Environmental Reporting and Its Expectations Gap in Malaysia - Chung, Stephanie Mien Yi (2005)
Recent research of corporate reporting practices has suggested that corporate environmental reporting in developing countries is typically deficient and not of standard to satisfy the information needs of various classes of report readers. This research explores whether a potential information demand/supply imbalance is due to differing perceptions between report preparers and report users as to the relative importance of various items of environmental performance information to the users’ decision making processes and explores whether an environmental reporting ‘expectations gap’ exists in Malaysia. The research surveyed the attitudes of senior executives of 130 Main Board listed companies in Malaysia (the preparers group) and the attitudes of 130 individuals from various categories of annual report users. In comparing the responses, significant differences between the views of users and the preparers were found to exist in relation to various issues associated with corporate environmental performance reporting.